Remitansi Internal dan Konsumsi: Implikasi bagi Kesejahteraan Rumah Tangga di Indonesia - Setiawan, Heru; Handra, Hefrizal; Ariyanto, Edi (SAFE-Network, 2023)
This research aims to examine the impact of internal remittances on household welfare in Indonesia. The focus of this study is not only to identify the direct influence of remittances on welfare but also to investigate how internal remittances affect household welfare through consumptive expenditures. The analytical tool used is Partial Least Squares-Structural Equation Modeling (PLS-SEM). The data used in this study is derived from the Indonesian Family Life Survey (IFLS) for the years 2007 and 2014. The research sample consists of 772 households with members who are internal migrant workers. The results of the study indicate that the improvement in household welfare is not only directly influenced by internal remittances but also by how these remittances are managed, particularly when used for consumptive spending. Other factors, such as the number of household members, also play a significant role in enhancing household welfare.